A Brief Study on the Implementation of Helical Cross-Flow Hydrokinetic Turbines for Small Scale Power Generation in the Indian SHP Sector - Jayaram Vijayan; Bavanish Balac Retnam (International Journal of Renewable Energy Development, 2022)
This article addresses the simulation and experiments performed on a Gorlov Helical Turbine (GHT) by altering the index of revolution of its helical blades. Gorlov Helical Turbine is a hydrokinetic turbine that generates energy from the perennial/tidal source. The paper serves a two-fold purpose: parametric optimisation of Gorlov Helical Turbine with respect to the index of revolution and viability of installing the turbines in river creeks. Nine models of turbines with a diameter of 0.600 m and a height of 0.600 m were generated with different indices of revolution and then subjected to simulation studies. A significant rise in the output torque of the turbine was not observed with the various indices of revolution, even as the probability of finding a section at every azimuthal position is likely to rise. Gavasheli's solidity ratio formula was used to formulate an expression for the output power. The output power as per analytical formulation is 1.11 W, which is of the order of output power obtained through simulation (0.951 W). The studies suggest that 0.25 remains the optimum value for the index of revolution of the helical blades. A model with 0.25 as the index of revolution was fabricated and tested at a river creek. The results were found to agree with the simulations accounting for the losses. The study results could encourage setting up hydrokinetic turbines in river creeks, thereby increasing the grid capacity of SHPs in India.